Fiatal Osztrákok. (Graz : Neue Galerie am Landesmuseum Joanneum, 1991)
Schmalix, Hubert ; Anzinger, Siegfried ; Mosbacher, Alois ; Kern, Josef ; Bohatsch, Erwin ; Klinkan, Alfred ; Wiedner, Wolfgang ; Priesch, Hannes ; Brandl, Herbert ; Danner, Josef ; ; Hikade, Karl ; Vopava, Walter ; B., Ona ; Kowanz, Brigitte ; Graf, Franz ; Schegel, Eva ; Talibe, Johann-Julian ; Bergler, Friedrich ; Haider, Ilse ; Molacek, Rudi ; Schuster, Michael ; Held, Georg ; Rosc, Irena ; Poschauko, Hans Werner ; Plank, Claudia ; Holler-Schuster, Günther ; Walter, Rudolf ; G.R.A.M. ; Stimm, Thomas ; Weinberger, Lois ; West, Franz ; Wurm, Erwin ; etc.
Fiatal Osztrákok / Junge Österreicher, Szombathelyi Képtár, Szombathely, 1991. szept. 20 - 1991. okt. 13.
Hongaars-Duits-Engels
kunstcatalogus
Keywords: Oostenrijk